On the estimations of solution of delated stochastic differential equations - Ryguła, Irena (Annales Mathematicae Silesianae, 1990)
The paper refers to the subject of the estimation of the difference between the solutions of two delated stochastic equations, which as a consequence gives also some criterions of the uniqueness for these equations. The results are obtained by using some integral inequalities and applying them to the more general class of equations with local integrable martingales.